Pharmacotherapeutic options for the management of Type 2 Diabetes Mellitus: literature review (Research, Society and Development, 2023)
In parallel with population aging and contemporary lifestyle, the incidence of individuals living with Type 2 Diabetes Mellitus (T2DM) is increasing, making it one of the main causes of morbidity and mortality in the world. In order to make a more assertive and individualized therapeutic choice and avoid micro and macrovascular complications secondary to T2DM, it is essential that health professionals are aware of all available pharmacotherapeutic resources. This work is a narrative review with the objective of discussing the particularities of the therapeutic options currently available for the management of T2DM. Books, clinical protocols, therapeutic guidelines and academic articles available in Scielo and Google academic databases were searched, considering works written in Portuguese or English. The search was performed in October 2022. The results reinforce that the importance of glycemic control to reduce the risk of complications is widely recognized by current therapeutic protocols and favor the adoption of evidence-based clinical approaches. There are many therapeutic options with demonstrated efficacy in achieving therapeutic goals, the main pharmacological classes are: biguanides, glitazones, sulfonylureas, glinides, alpha-glucosidase inhibitors, insulins, DDP-4 inhibitors, GLP-1 agonists and SGLT2 inhibitors. Treatment options, however, need to be individualized according to clinical characteristics (risk of hypoglycemia, age, comorbidities, disease stage, T2DM complications, tolerability and adverse effects), sociodemographic characteristics, preferences and individual values, favoring the person-centered care.